Influence of Sodium Hydroxide (NaOH) on Green and Fired Pellet Properties - Basha S.M.; Ramesh M.S.S.; Dwarapudi S.; Misra S.; Mahobia G.S.; Sinha R.K.; Vandana G.; Paul I. (My University, 2025)
Globally, bentonite is being used as a binder in iron ore pelletizing due to its high swelling index, thermal resilience, and water absorption capacity. However, the conventional use of bentonite contributes to increased gangue content (Al2O3 and SiO2) in pellets, subsequently affecting blast furnace operations in terms of high solid fuel consumption, low productivity, and high slag rates. In this work, sodium hydroxide has been used with bentonite to reduce its consumption without affecting the pellet properties. Pellets are prepared by varying the NaOH addition from 0 to 0.1 pct at an interval of 0.02 pct. Green and fired pellets were tested for green compressive strength (GCS), dry compressive strength (DCS), drop number, cold compressive strength (CCS), Hoogoven simulations (HOSIM), softening-melting, and swelling index (SI). The interaction between hematite and bentonite was studied using molecular modeling simulations (ReaxFF MD). Microstructural studies (optical and SEM-EDS) of pellets were carried out for phase quantification and to assess the chemical composition of slag phases. Besides, FactSage simulations were performed to validate the slag phase formation. It is inferred that a 50 pct reduction in bentonite consumption is possible at 0.04 pct NaOH with a 12 pct improvement in CCS. Laboratory results were validated for a seven-million-tonne pellet plant with 0.02 and 0.04 pct NaOH dosage. Plant trial shows that there is an 18 and 39 pct reduction in bentonite consumption with the addition of 0.02 and 0.04 pct NaOH dosages, respectively. Graphical Abstract: (Figure presented.) © The Minerals, Metals & Materials Society and ASM International 2024.